Diagnostic significance of hormonal, biochemical and echographic methods of research in postmenopausal women with endometrial cancer - M. A. Garashova; E. M. Alieva (Опухоли женской репродуктивной системы, 2019)
Objective: to determine the significance of hormonal, biochemical, echographic research methods in the diagnosis of endometrial cancer.Materials and methods. Fifty patients with endometrial cancer with varying degree of severity were examined. The average age of patients with endometrial cancer was 62.4 ± 1.0 years. The study of the prevalence of the tumor process made it possible to establish that the frequency of patients with stage I was 68 %, with stage II – 30 %, and with stage III – 2 %.Results and conclusions. According to hormonal studies, the statistical significance of a decrease in the luteinizing hormone/follicle-stimulating hormone ratio (0.69 ± 0.09), an increase in prolactin levels (467.3 ± 35.1 ng/ml), dehydroepiandrosterone sulfate (92.9 ± 14.4 ng/ml), estrone (101.6 ± 6.29 ng/ml), progesterone (1.9 ± 0.52 ng/ml), as well as a decrease in estradiol (17.4 ± 3.4 pg/ml) and testosterone (0.5 ± 0.02 ng/ml) levels. According to echographic studies, a pathological increase in the thickness of the endometrium (24.9 ± 2.7 mm) was established with the background of increasing the size of the uterus and ovaries. Indicators of biochemical studies in patients with endometrial cancer in the postmenopausal period were within the range of physiological fluctuations.